Sistem Informasi Hasil Tani Nagari Lolo Berbasis Web - Turaina, Rifa; Defiariany, Defiariany; Azha, Silvia Netri (UIN Imam Bonjol Padang, 2021)
Farmer Product Information System in Nagari Lolo Pantai Cermin District Solok Regency is a web-based system that is used to manage and at the same time organize farmer data, farm products in Nagari Lolo Pantai Cermin District Solok Regency. The information system is created using the programming language Framework Codeigniter, PHP and MYSQL by using object-oriented methods that aid system development, namely Unified Modeling Language (UML). At this time the data of farmers, crop yields, crops are still managed with the help of Microsoft Excel and Microsoft Word, in the delivery of information still by going directly to the field and contacting each jorong. With the web-based information system of agricultural products, the information about agricultural products, as well as information on the nagari is more effective and the data storage of farmers and farm results is stored in a database.